Association of Bitter Metabolites and Flavonoid Synthesis Pathway in Jujube Fruit - Shi, Qianqian; Li, Xi; Du, Jiangtao; Liu, Yu; Shen, Bingqi; Li, Xingang (Frontiers in Nutrition, 2022)
Jujube is rich in nutrients and can be eaten fresh or made into dried fruit, candied fruit and preserved fruit. Its slightly bitter peel affects nutritional value and commercial value, but the mechanism of the formation of bitter substances is still unclear. We dynamically analyzed the biosynthesis of jujube peel bitterness and related nutrient metabolites through the transcriptome and metabolome. The results demonstrated that flavonoids were the main bitter substances in ‘Junzao’ jujube fruit skins and a total of 11,106 differentially expressed genes and 94 differentially abundant flavonoid metabolites were identified. Expression patterns of genes in the flavonoid synthesis pathway showed that flavonol synthase (FLS) expression was significantly correlated with quercetin content. Transient overexpression and virus induced gene silencing (VIGS) of ZjFLS1 and ZjFLS2 in jujube fruits and sour jujube seedlings significantly affected flavonol accumulation, especially the content of quercetin-3-O-rutinoside. Moreover, in vitro enzymatic reactions showed that ZjFLS1 and ZjFLS2 could catalyze the formation of quercetin from dihydroquercetin. These findings indicate that ZjFLS gene is the key gene in the biosynthesis of bitter substances in jujube fruit skins and provide basis for the research on the development of functional nutrients in jujube and the synthesis mechanism of bitter compounds.